2012
DOI: 10.1007/s00284-012-0229-x
|View full text |Cite
|
Sign up to set email alerts
|

Flavone Reduces the Production of Virulence Factors, Staphyloxanthin and α-Hemolysin, in Staphylococcus aureus

Abstract: Staphylococcus aureus is a leading cause of nosocomial infections due to its resistance to diverse antibiotics. This bacterium produces a large number of extracellular virulence factors that are closely associated with specific diseases. In this study, diverse plant flavonoids were investigated to identify a novel anti-virulence compound against two S. aureus strains. Flavone, a backbone compound of flavonoids, at subinhibitory concentration (50 μg/mL), markedly reduced the production of staphyloxanthin and α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 24 publications
(34 reference statements)
2
47
0
Order By: Relevance
“…Since many plant bacterial pathogens use type III secretion systems to cause disease and sense flavonoids 30 , it is possible that some of these compounds may have evolved as a consequence host-pathogen interactions. Moreover, flavonoids have also been reported to target other anti-infective properties such as expression of virulence genes 31,32 , toxin activity 33-35 , quorum sensing 36-39 and biofilm formation 40,41 in bacterial pathogens as well as attenuate destructive host inflammation 42-44 . Given the broad pharmacological activities of flavonoids, these plant metabolites may affect microbial virulence mechanisms, including type III protein secretion substrates shown here, in addition to host pathways for their anti-infective properties in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Since many plant bacterial pathogens use type III secretion systems to cause disease and sense flavonoids 30 , it is possible that some of these compounds may have evolved as a consequence host-pathogen interactions. Moreover, flavonoids have also been reported to target other anti-infective properties such as expression of virulence genes 31,32 , toxin activity 33-35 , quorum sensing 36-39 and biofilm formation 40,41 in bacterial pathogens as well as attenuate destructive host inflammation 42-44 . Given the broad pharmacological activities of flavonoids, these plant metabolites may affect microbial virulence mechanisms, including type III protein secretion substrates shown here, in addition to host pathways for their anti-infective properties in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in an in vitro enzyme assay, Cu, along with Zn and Fe, was shown to inhibit the kinase activity of SaeS [42], possibly competing with Mg in SaeS. Finally, the following molecules have been reported to inhibit the expression of the sae -operon or some members of Sae-regulon and have a potential to be a Sae inhibitor: florfenicol [55], corilagin [56], licochalcone A [57], thymol [57], the enoyl-acyl carrier protein reductase inhibitor AFN-1252 [58], cerulenin [59], subinhibitory concentration of linezolid [60], Manuka honey [61], and flavone [62]. …”
Section: Signalsmentioning
confidence: 99%
“…Recently, we reported that a plant flavone (Lee et al 2012) and a bacterial signaling molecule indole (Lee et al 2013) reduced the production of staphyloxanthin and α-hemolysin.…”
Section: Introductionmentioning
confidence: 98%